Realistic ocean initial condition for stimulating the successful prediction of extreme cold events in the 2020/2021 winter - Fei Zheng; Haolan Ren; Renping Lin; Jiang Zhu (Climate Dynamics, 2023)

Can Eurasia Experience a Cold Winter under a Third-Year La Niña in 2022/23? - Fei Zheng; Bo Wu; Lin Wang; Jingbei Peng; Yao Yao; Haifeng Zong; Qing Bao; Jiehua Ma; Shuai Hu; Haolan Ren; Tingwei Cao; Renping Lin; et al. (Advances in Atmospheric Sciences, 2023)

Comparative Analysis of Two Approaches for Correcting the Systematic Ocean Temperature Bias of CAS-ESM-C - Mengjiao Du; Fei Zheng; Jiang Zhu; Renping Lin; Kan Yi (Journal of Marine Science and Engineering, 2021)
Currently, several ocean data assimilation methods have been adopted to increase the performance of air–sea coupled models, but inconsistent adjustments between the sea temperature with other oceanic fields can be introduced. In the coupled model CAS-ESM-C, inconsistent adjustments for ocean currents commonly occur in the tropical western Pacific and the eastern Indian Ocean. To overcome this problem, a new ensemble-based bias correction approach—a simple modification of the Ensemble Optimal Interpolation (EnOI) approach for multi-variable into a direct approach for a single variable—is proposed to minimize the model biases. Compared with the EnOI approach, this new approach can effectively avoid inconsistent adjustments. Meanwhile, the comparisons suggest that inconsistent adjustment mainly results from the unreasonable correlations between temperature and ocean current in the background matrix. In addition, the ocean current can be directly corrected in the EnOI approach, which can additionally generate biases for the upper ocean. These induced ocean biases can produce unreasonable ocean heat sinking and heat storage in the tropical western Pacific. It will generate incorrect ocean heat transmission toward the east, further amplifying the inconsistency introduced through the tropical air–sea interaction process.

Influence of the Eastern Pacific and Central Pacific Types of ENSO on the South Asian Summer Monsoon - Fangxing Fan; Renping Lin; Xianghui Fang; Feng Xue; Fei Zheng; Jiang Zhu (Advances in Atmospheric Sciences, 2021)

ENSO Frequency Asymmetry and the Pacific Decadal Oscillation in Observations and 19 CMIP5 Models - Renping Lin; Fei Zheng; Xiao Dong (Advances in Atmospheric Sciences, 2018)

Evaluation of ocean data assimilation in CAS-ESM-C: Constraining the SST field - Xiao Dong; Renping Lin; Jiang Zhu; Zeting Lu (Advances in Atmospheric Sciences, 2016)

Chinese contribution to CMIP5: An overview of five Chinese models’ performances - Tianjun Zhou; Xiaolong Chen; Lu Dong; Bo Wu; Wenmin Man; Lixia Zhang; Renping Lin; Junchen Yao; Fengfei Song; Chongbo Zhao (Journal of Meteorological Research, 2014)